Surviving the Pandemic: Remote Working in the Maltese Public Service During the Covid-19 Outbreak - Bezzina, Frank; Cassar, Vincent; Marmara, Vincent; Said, Emanuel (Frontiers in Sustainability, 2021)
This study examines how human resources in the Maltese Public Service adopt new work practices in response to COVID-19 public health measures during the first wave of the pandemic. We analyze the data we collected through seven focus group discussions and ten in-depth interviews with Public Service employees and managers in a diversity of ministries and roles. Our study reveals that Public Service policies promoting remote working relied exclusively on the service's IT infrastructure. However, the ability to respond to customer needs effectively in a time of surging demand relied entirely on effective employees' access to responsive and efficient ICT support as well as employees' prior experience with remote work modes and their predisposition to change to remote working. Adopting remote working modes uncovered inherent weaknesses in the Public Service IT infrastructure that put additional strain on the Government's centralized IT support function, especially when Public Service employees adopted tools not supported by the centralized IT support. In circumstances where centralized IT support was ineffective, Public Service employees relied on their own knowledge resources which they informally shared in groups of practice or employed operant resources (or tacit knowledge) to achieve service level objectives. These observations suggest that in times when organizations respond to immediate and unprecedented change, human resources seek to adapt by relying on tacit knowledge that is shared among people in known (often informal) groups of people with a common interest or role.